Perovskite/Carbon Composites: Applications in Oxygen Electrocatalysis - Zhu, Y.; Zhou, W.; Shao, Zongping (Wiley, 2017)
Oxygen electrocatalysis, i.e., oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), plays an extremely important role in oxygen-based renewable-energy technologies such as rechargeable metal-air batteries, regenerative fuel cells and water splitting. Perovskite oxides have recently attracted increasing interest and hold great promise as efficient ORR and OER catalysts to replace noble-metal-based catalysts, owing to their high intrinsic catalytic activity, abundant variety, low cost, and rich resources. The introduction of perovskite-carbon interfaces by forming perovskite/carbon composites may bring a synergistic effect between the two phases, thus benefiting the oxygen electrocatalysis. This review provides a comprehensive overview of recent advances in perovskite/carbon composites for oxygen electrocatalysis in alkaline media, aiming to provide insights into the key parameters that influence the ORR/OER performance of the composites, including the physical/chemical properties and morphologies of the perovskites, the multiple roles of carbon, the synthetic method and the synergistic effect. A special emphasis is placed on the origin of the synergistic effect associated with the interfacial interaction between the perovskite and the carbon phases for enhanced ORR/OER performance. Finally, the existing challenges and the future directions for the synthesis and development of more efficient oxygen catalysts based on perovskite/carbon composites are proposed.